Post-traumatic stress and dimensions of exposure to violence: the individual response - Esprey, Yvette (My University, 1996)
At a primary level the current study sought to investigate the post-traumatic stress responses of a sample of black township residents who were victims and witnesses of continuous civil violence [Abbreviated abstract. Open document to view full version]
Thesis (M.A.(Industrial Psychology)--University of the Witwatersrand, Arts Faculty, 1996
Keywords: Post-traumatic stress disorder; Violence--South Africa; Blacks--Mental health--South Africa